On Capability of the Nonlinear k-ε Turbulence Model in the Prediction of Non-Isotropic Stratified Flows. (September 2015) - Shamsnia, H.; Hejazi, K.
The commonly used linear k-ε turbulence model has been shown to be incapable of accurate prediction of turbulent flows where non-isotropy is present. Two types of non-isotropic flows which are due to stratification, and consequently variation of density through vertical layers, are saline water flow and the stratified flows due to temperature gradients which both have a wide range of applications in environmental fluid mechanics. In this study a nonlinear k-ε turbulence model firstly presented by Speziale [1] has been deployed and implemented in the hydrodynamic model WISE (Width Integrated Stratified Environments), a 2DV numerical model originally developed by Hejazi [2]. The energy equation has been also added and solved in the hydrodynamic model. The model solves the fully nonlinear Navier-Stokes equations based on an ALE (Arbitrary Lagrangian- Eulerian) description. The simulated results have been compared against the measured values reported in the literature and have shown acceptable agreements. The predictions are also compared with the results of the original model which has employed a standard buoyant k-ε turbulence model, showing the superiority of the non-linear k-ε developed herein compared to the linear k-ε turbulence model in the prediction of non-isotropic flows especially for the velocity profiles.